Inhibition Biofilm of Medicinal Plants: A Review (International Journal of Innovative Research in Engineering & Management, 2021)
Nowadays there is rising threat of multi-drug resistant bacteria  mainly occurring due to the indiscriminate use of antibiotics.  The bacteria tend to aggregate on many surfaces forming 3D  structures called biofilms which are akin to the tissue  organization of higher organisms. These biofilms help the  bacteria regarding the spread of antibiotic resistance and  increase in their pathogenicity. These biofilms are maintained  by a signalling network known as quorum signalling. QS is  dependent upon the presence of auto & trans-inducers which  affect bacterial transcription. Hence the aim of many  researchers is to inhibit QS. In this regard, medicinal plants  have become important and the aim of this review is to  highlight the role of QS in biofilm formation and the plants  which can inhibit QS. Proper identification of plants having  such roles could be a potential strategy to target multi drug  resistant bacteria in future studies.
Keywords: N-Acyl Homoserine Lactone (AHL); Bacteria; Biofilms; Medicinal plants; Multi-drug resistance; Phyto-chemicals; Phyto-molecules; Quorum sensing